Assessment of Tumor markers, C-reactive Protein, Cortisol and Total Plasma Peroxides Levels in Uterine Leiomyoma Patients - Moses Akiibinu; Adebayo Amballi; Olusoji Jagun; Ajibola Adisa; Susan Akiibinu; Adeolu Amusan; Ibukun Jimo; Ayodele Olalekan (European Scientific Journal, ESJ, 2017)
Objective: The pathophysiology of uterine leiomyoma is yet to be fully understood. This study determined the status of cortisol, C-reactive protein, total plasma peroxide and selected tumor markers in uterine leiomyoma patients. Materials and Methods: Forty-eight individuals (aged 25-45 years) with uterine leiomyoma (nodules=1-4; size=5-120mm) were recruited for this study. Forty apparently age-matched normal individuals without uterine leiomyoma served as controls. The patients and controls were selected after confirmation of the status of uterine leiomyoma by ultrasound imaging technique. The plasma levels of total plasma peroxides(TPP), cortisol, carcino-embryonic antigen(CEA), alpha fetoprotein (AFP), carbohydrate antigen 125(CA125) and C-reactive protein(CRP) were determined in them using spectrophotometry, enzyme linked immunosorbent assay and single radial immunodiffusion (Maccini) methods respectively. Results: The result shows significantly higher levels of TPP (p0.05) changes in the plasma levels of cortisol, CEA and AFP in the leiomyoma patients when compared with the controls. Significant (r=0.521, p=0.03) correlation existed between the number of myoma nodules and the levels of CRP in the leiomyoma patients. The size of the nodules correlated significantly (r=0.47, p=0.04) with the plasma levels of TPP. Conclusion: Elevated levels of CRP and TPP could indicate oxidative stress and inflammatory response in uterine leiomyoma patients. The induced inflammation and oxidative stress may increase with increase in number and size of the myoma nodules respectively. Higher level of CA125 could be a feature of uterine leiomyoma.